Pseudomonas fluorescens as Plant Growth Promoting Rhizobacteria (PGPR) - Atiqahh Muthiah; Linda Advinda; Azwir Anhar; Irma Leilani Eka Putri; Siska Alicia Farma (Jurnal Serambi Biologi, 2023)
The continuous use of chemical fertilizers will cause negative impacts such as pollution of the agricultural environment. This needs to be addressed by using Plant Growth Promoting Rhizobacteria (PGPR) which can trigger plant growth. Pseudomonas fluorescens is a bacterium that lives in the rhizosphere and is included in PGPR bacteria. P. fluorescens has the ability to produce siderophores, IAA, dissolve phosphate and fix nitrogen. Therefore, these bacteria can increase growth, provide plant nutrients and inhibit pathogens that cause plant diseases. This study aims to collect and analyze articles related to Pseudomonas fluorescens as PGPR. This type of research is research that uses the literature review method and literature collection using internet sources from the Google Scholar database. This stage consists of identification, screening, eligibility and acceptance. Based on the articles collected, it was found that P. fluorescens as PGPR can increase plant growth by having the ability to produce IAA, dissolve phosphate, produce siderophores and fix nitrogen.